Polyaniline/wheat Husk Ash Nanocomposite Preparation and Modeling Its Removal Activity with an Artificial Neural Network - Fatemeh Ghanbary (Science Faculty of Chiang Mai University, 2019)
In this work the removal efficiency of malachite green (MG) by using a nanocomposite was investigated. For preparation this nanocomposite the polyaniline (PANI) was coated on wheat husk ash (WHA). This nanocomposite was analyzed by X-ray diffraction (XRD) and scaning electron microscopy (SEM). The removal rate is strongly dependent on the PANI/WHA initial dosage, MG initial concentration, UV light intensity and irradiation time. The effect of these parameters has been studied and the optimum operational conditions was found. To predict the removal of MG in the presence of PANI/WHA nanocomposite an artificial neural network model (ANN) was developed. The comparison between the predicted results by designed model and the experimental data proved that modeling for removal process of MG using ANN was a precise method to predict the extent of MG removal under different conditions.